In vitro effectiveness of Brazilian brown propolis against Enterococcus faecalis - Hévelin Couto PIMENTA; Ivana Maria Povoa VIOLANTE; Carlo Ralph de MUSIS; Álvaro Henrique BORGES; Andreza Maria Fábio ARANHA (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to evaluate the in vitro antimicrobial activity of Brazilian brown propolis as an intracanal medication against Enterococcus faecalis. Thirty dentin discs prepared from intact freshly extracted bovine maxillary central incisors were infected with E. faecalis for 21 days. The specimens were distributed into six groups according to the medicament used as follows: G1- calcium hydroxide paste; G2- Carbowax 400 (control group); G3- 20% brown propolis paste; G4- 40% brown propolis paste; G5- 20% brown propolis paste + calcium hydroxide paste; and G6- 40% brown propolis paste + calcium hydroxide paste. The experimental pastes were placed into the canal lumen and left for 14 days. After each period, irrigation was performed with sterile saline to remove the medicament, and the canals were dried with sterile paper points. The dentin chips were removed from the canals with sequential sterile round burs at low speed and were immediately collected in separate test tubes containing BHI broth. The tubes were incubated at 37°C, and microbial growth was analyzed by spectrophotometry after 15 days. All the experimental medications significantly reduced the number of viable bacteria. The G4 and G5 pastes were more effective than the G1 paste, with 35.8%, 41%, and 21.3% antibacterial activity, respectively. Brazilian brown propolis shows antibacterial capacity against E. faecalis.